Safranbolu Şer‘iyye Sicillerinde Geçen Eşya, Lakap ve Yer İsimleri / The Dictionary of Wares, Nicknames and Place Names Mentioned in the Sheria Registries of Safranbolu - Tekin, Zeki; Ceylan, Hatice (Journal of History Culture and Art Research, 2017)
Abstract The Safranbolu Sheria Registries are significant official documents which give us tremendous insights in terms of the social life in the Ottoman Empire. These notebooks, which were kept by the Kadis (judges) who were responsible of governing a substantial part of town life, give us the possibility to take a closer look at the social-cultural diversity of our history un known yet. These are very important first hand-source documents in terms of law history social history, military history, finance history, local history, city history, place and people’s names as well as medicine history, diplomacy history, conmercial and agri cultural lives. They also serve our culture and our history by covering and embodying words, terms, nicknames, titles, private names, names of places and objects as well as cultural elements. With this explicit transcription study of the Safranbolu Sheria Registries, we also aimed to help those who wish to make a study about this particular subject. Öz Safranbolu Şer‘iyye Sicilleri, Osmanlı toplum hayatını net bir şekilde yansıtan son derece önemli resmî evraklardır. Şehir hayatının önemli bir kısmını yöneten kadılar tarafından tutulan bu defterler, sosyo-kültürel çeşitlilik açısından tarihimizin bilinmeyen yönlerini aydınlatma ve belgelendirme olanağı verir. Bu evraklar hukuk tarihi, sosyal tarih, askerî tarih, iktisadî tarih, yerel tarih, şehir tarihi, yer ve kişi adları, tıp tarihi, diplomasi tarihi, ticaret ve zirâî yaşam açısından önemli olan birinci el kaynak niteliğindedir. Bünyesinde barındırdığı kelime, kavram, lakap, unvan, özel isimler, yer isimleri, eşya adları ve kültürel unsurları ile tarihimize ve kültürümüze hizmet etmektedir. Safranbolu’ya ait transkripsiyonu yapılan şer‘iyye sicillerinin taranması sonucu ortaya çıkan bu çalışma ile konu üzerine araştırma yapanlara kolaylık sağlanması amaçlanmıştır.